DESIGN AND BIOACTIVITY ASSESSMENT OF A TINOSPORA-BASED HERBAL ELIXIR WITH MULTIFUNCTIONAL THERAPEUTIC POTENTIAL - Matte Prasad S; Tate Parnika J; Udeshi Nupur Y; Vishwakarma Shrushti P; Waghmare Anjali D; Pattar Harsh M; Borhade Aditya S; Wagh Gayatri A; Dr. Mahajan Kiran C; Dr. Dama Ganesh Y (The Bioscan, 2026)
Particularly in India and other Asian nations, medicinal herbs are becoming widely recognized as alternative treatments for preventing a variety of ailments. The majority of plant-based herbal remedies, however, have not yet gained global scientific recognition. "Wild. cordifolia Tinospora”, “Giloy" or “Guduchi”, one of the most promising plant species of Tinospora, has been extensively studied. It is employed in a number of traditional medicines to treat a variety of illnesses, including immunological and metabolic problems, diabetes, cancer, heart disease, and infectious diseases. Numerous bioactive phytochemical components have been discovered and isolated from T. cordifolia's stem, root, and whole plant. Over the past twenty years, T. cordifolia's many pharmacological effects have been the subject of ongoing research. metabolic diseases including diabetes mellitus and obesity are linked to oxidative stress, insulin resistance, hyperglycemia, dyslipidemia, and cardiovascular problems. Herbal formulations have drawn a lot of attention due to their safety, potency, and therapeutic potential because long-term usage of synthetic medications can have negative effects. The goal of the current study was to create and assess a multipurpose polyherbal elixir for the treatment of obesity and diabetes mellitus that included Tinospora cordifolia as the main ingredient, ginger extract, garlic extract, green tea extract, and stevia. Because Tinospora cordifolia contains alkaloids, glycosides, flavonoids, diterpenoids, and phenolic chemicals, it has been reported to have anti-diabetic, hypolipidemic, antioxidant, and immunomodulatory activities. The phytochemical analysis verified the existence of important bioactive components with anti-obesity and anti-diabetic properties. With a pH of about 6.0, a refractive index between 1.3308 and 1.3501, and a viscosity appropriate for oral administration, the prepared elixir demonstrated acceptable physicochemical characteristics. Maximum absorbance was revealed by UV spectrophotometric measurement at: The formulation's physical stability is indicated by λ max = 277.5 nm. Cordifolia, ginger, garlic, and green tea may all work together to enhance glucose metabolism, lower oxidative stress, control lipid profiles, and encourage fat metabolism. Consequently, the polyherbal elixir may be a viable herbal therapeutic preparation for the treatment of diabetes mellitus and obesity. To prove safety and effectiveness, more pharmacological and clinical research is needed.